2013
DOI: 10.1128/jb.00344-13
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Analysis of the groES-groEL1 , groEL2 , and dnaK genes in Corynebacterium glutamicum: Characterization of Heat Shock-Induced Promoters

Abstract: Drs. Barreiro and Martín take sole responsibility for these instances of data duplication and would like to apologize to the readers, reviewers, and editors of both the Journal of Bacteriology and Microbiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…4). The same TSPs were found in C. glutamicum ATCC 13032 and C. glutamicum CCM251 for some promoters (Barreiro et al, 2004;Engels et al, 2004;Halgasova et al, 2001), although a few nucleotides within the promoter regions differ in the sequences of these strains. According to the results of the gene expression profiling and sequence inspection of potential operons, the H -regulon is formed by 45 genes that constitute 29 transcriptional units in C. glutamicum R (Ehira et al, 2009).…”
Section: Sigh-dependent Promoterssupporting
confidence: 60%
See 1 more Smart Citation
“…4). The same TSPs were found in C. glutamicum ATCC 13032 and C. glutamicum CCM251 for some promoters (Barreiro et al, 2004;Engels et al, 2004;Halgasova et al, 2001), although a few nucleotides within the promoter regions differ in the sequences of these strains. According to the results of the gene expression profiling and sequence inspection of potential operons, the H -regulon is formed by 45 genes that constitute 29 transcriptional units in C. glutamicum R (Ehira et al, 2009).…”
Section: Sigh-dependent Promoterssupporting
confidence: 60%
“…The activity of C. glutamicum H is most probably regulated by the anti-sigma factor RshA via a similar mechanism at the posttranscriptional level. The crucial role of H in the induction of the genes involved in heat stress response in C. glutamicum ATCC 13032 was shown in studies of the genes coding for ATP-dependent Clp proteases (Engels et al, 2004) and heat shock proteins and regulators (Barreiro et al, 2004;Ehira et al, 2009;Kim et al, 2005). Many Hregulated genes were detected in the study of heat shock response by DNA microarrays using sigH-disrupted and sigH-overexpressing strains of C. glutamicum R. The respective H -dependent promoters were localized by mapping the transcriptional start points of these genes (Ehira et al, 2009) (Fig.…”
Section: Sigh-dependent Promotersmentioning
confidence: 98%
“…Out of the promoters previously found to be dependent on the primary-like alternative sigma factor r B , we have chosen the promoter of the pqo gene encoding pyruvate:quinone oxidoreductase [21] (Ppqo), expressed mainly in the stationary growth phase [4]. To test the effects of deletions of stress-responding ECF sigma factors, we have chosen promoters of the dnaK-grpE-dnaJ-hspR operon encoding proteins involved in heat-shock response [1], the dnaJ2 gene encoding a chaperone protein [2] and the clgR gene encoding a transcriptional regulator [6]. It was previously found that all these genes are expressed from two promoters: a housekeeping one (i.e., most probably r A -dependent) and a r H -dependent one.…”
Section: Resultsmentioning
confidence: 99%
“…The fragment with promoter Pper (96 bp) [13] was amplified using the plasmid pGA1 from C. glutamicum LP-6 as a template resulting in the construct pRLG770Pper. The fragment with promoter P2dnaK (109 bp) [1] was amplified using C. glutamicum ATCC13032 genome DNA as a template to provide the construct pRLG770P2dnaK. Promoter fragments Ppqo, P1clgR, and P2dnaJ2 were prepared by dimerization of oligonucleotides listed in Table S1 to provide the constructs pRLG770Ppqo, pRLG770P2dnaJ2, and pRLG770P1clgR, respectively.…”
Section: Construction Of Promoter-carrying Dna Templates For In Vitromentioning
confidence: 99%
“…The fragments with promoters P2dnaK (109 bp) ( Barreiro et al 2004) and PsigB (179 bp) (Halgasova et al 2001) were amplified using C. glutamicum ATCC13032 genome DNA as a template and cloned in the EcoRI-HindIII sites of the vector pRLG770 to provide the constructs pRLG770P2dnaK and pRLG770PsigB, respectively. The P2dnaK, which is presumably recognized by σ H (Ehira et al 2009), was separated from another mapped promoter of the dnaK gene, the housekeeping P1 ( Barreiro et al 2004), by cloning an upstream region. The fragment with Pper (96 bp; Nešvera et al 1997) was amplified using the plasmid pGA1 from C. glutamicum LP-6 as a template resulting in the construct pRLG770Pper.…”
Section: Construction Of Promoter-carrying Plasmid Templates For In Vmentioning
confidence: 99%